2021
DOI: 10.1002/jcla.23893
|View full text |Cite
|
Sign up to set email alerts
|

miR‐92a promotes cervical cancer cell proliferation, invasion, and migration by directly targeting PIK3R1

Abstract: Objective To clarify the role of miR‐92a in regulating the malignant progression of cervical cancer and its specific molecular mechanism. Methods qRT‐PCR was used to detect the differential expression of miR‐92a in cervical cancer and adjacent tissues. The effects of overexpression of miR‐92a on the proliferation, migration, and invasion of HeLa and SiHa cells were tested. Luciferase assays and rescue experiments were used to investigate the regulatory mechanism of miR‐92a on its downstream gene PIK3R1 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…MicroRNAs (miRNAs) are small noncoding RNA molecules that combine with the 3′-untranslated region (UTR) of target mRNAs and modulate the expression of genes [ 13 ]. miRNAs affect the progression of several cancer types, including CC, by altering the biological activities of pro-or suppressor genes [ 14 ]. For example, miR-186-3p reduces tumorigenesis of CC by targeting IGF1 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNA molecules that combine with the 3′-untranslated region (UTR) of target mRNAs and modulate the expression of genes [ 13 ]. miRNAs affect the progression of several cancer types, including CC, by altering the biological activities of pro-or suppressor genes [ 14 ]. For example, miR-186-3p reduces tumorigenesis of CC by targeting IGF1 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…PIK3R1 is poorly expressed in most malignancies and is associated with tumor progression and metastasis [ 46 ]. Overexpression of PIK3R1 reversed CC proliferation, migration, and invasion which were triggered by overexpression of miR-92a [ 47 ]. In addition, gene expression analysis of CC revealed that epithelial-mesenchymal transition (EMT)-related genes PIK3R1 and STAT3 are potential biomarkers and/or therapeutic targets for CC [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have confirmed using ROC curves that miR-92a-5p expression has high specificity and sensitivity at the optimal threshold in the detection of both low-grade squamous intraepithelial lesions (LSILs) and high-grade squamous intraepithelial lesions (HSILs) (LSILs: 95% sensitivity, 87% specificity; HSILs: 94% sensitivity, 87% specificity) ( Azimi et al, 2021 ). Wang et al combined qRT-PCR, luciferase assays, and rescue experiments to confirm that miR-92a, which is significantly upregulated in CC tissues, is negatively correlated with its downstream target gene PIK3RI ( Wang et al, 2021 ). Liu et al found a negative relationship between the overall survival of CC patients and miR-92a-3p, and observed that miR-92a-3p is able to promote CC stem cell proliferation, invasion, and cell cycle transition ( Liu et al, 2021b ).…”
Section: Mirna Interference With CC Developmentmentioning
confidence: 99%